Orexin Receptor Antagonism in Painful Diabetic Neuropathy: A Phase 2 Trial With Filorexant. Issue 1 (January 2018) - Joseph Herring, W.; Ge, Joy Y.; Jackson, Saheeda; Assaid, Christopher; Connor, Kathryn M.; Michelson, David
Abstract : Objectives: To evaluate whether orexin receptor antagonism with filorexant provides pain relief in patients with painful diabetic neuropathy (PDN). Methods: In this double-blind, placebo-controlled, enriched-enrollment, randomized-withdrawal proof-of-concept study, patients with PDN (aged 18 to 75 y) entered a 2-week, single-blind active run-in period with filorexant 10 mg nightly, before randomization 1:1 to placebo or filorexant in a 2-week, double-blind treatment period. The primary efficacy endpoint was time to efficacy failure among "primary responders" (≥30% decrease in evening pain intensity during the run-in). Secondary endpoints were time to efficacy failure among "all responders" (≥20% decrease in evening pain intensity during the run-in) and mean change from baseline in evening pain intensity throughout last 3 days of the double-blind period. Results: Of the 182 patients treated during the run-in, 170 were randomized in the double-blind period, including 65 primary responders and 88 responders. There was no significant difference in proportion of patients with efficacy failure during the double-blind period with filorexant versus placebo among primary (24.3% vs. 32.1% [ P= 0.411]) or all (34.0% vs. 43.9% [nominal P= 0.302]) responders or in mean change from baseline in evening pain intensity scores (estimated treatment difference: −0.587 [ P= 0.269], primary; −0.687 [ P= 0.108], all). Adverse events were reported by 24.7% of patients during the run-in. A higher proportion of patients treated with filorexant versus placebo reported adverse events during the double-blind period (23.9% vs. 13.4%). Discussion: These data do not provide evidence for the efficacy of nightly filorexant for the treatment of PDN. Abstract : Supplemental Digital Content is available in the text.